If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -9) = 20 + -30 Reorder the terms: 4(-9 + 5x) = 20 + -30 (-9 * 4 + 5x * 4) = 20 + -30 (-36 + 20x) = 20 + -30 Combine like terms: 20 + -30 = -10 -36 + 20x = -10 Solving -36 + 20x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 20x = -10 + 36 Combine like terms: -36 + 36 = 0 0 + 20x = -10 + 36 20x = -10 + 36 Combine like terms: -10 + 36 = 26 20x = 26 Divide each side by '20'. x = 1.3 Simplifying x = 1.3
| 2u+13=53 | | x-2/3=1-x/2 | | 8x-2y=16y | | f(x)=-2x-15 | | 0.06(y-6)+0.18y=0.12y-0.03(50) | | (15-2x)^(1/2)=x | | 3x+1=5(x-5) | | -14+7+4b=1+5b | | x/7-11/4=x/14-1/28 | | 23/n=8/7 | | 178/12 | | 37=3v-11 | | 4x^3-48x^2-144x=0 | | 4/9x+4=-5/9x-2 | | 8x^2+2x=x-6 | | 9/4log[5]x=7 | | -18+22=-2(x+7) | | 3+6x+3=0 | | 5t-9t= | | 10y=14y-20 | | (6x)+5=[(5x)-(12)] | | 4x^2-11x+22=6x+4 | | -4(2x+8)=4-2 | | 0.20x+.25(50)=21.5 | | 0.5-11= | | (6x)+5=(5x)-(12) | | 2(4x-3)-x=5 | | 4r-23=-14+r | | 2-3(x+2)=5x-4 | | x^2-10x+43=5x-1 | | (6x)+5=(5x)-12 | | 45+24h=405 |